Treatment and Prophylactic Strategy for Coxiella burnetii Infection of Aneurysms and Vascular Grafts: A Retrospective Cohort Study. Issue 12 (March 2016) - Eldin, Carole; Mailhe, Morgane; Lions, Caroline; Carrieri, Patrizia; Safi, Hazem; Brouqui, Philippe; Raoult, Didier
Abstract : Abstract: Coxiella burnetii vascular infections continue to be very severe diseases and no guidelines exist about their prevention. In terms of treatment, the benefit of the surgical removal of infected tissues has been suggested by 1 retrospective study. We present a case of a C burnetii abdominal aortic graft infection for which we observed a dramatic clinical and biological recovery after surgery. We thus performed a retrospective cohort study to evaluate the impact of surgery on survival and serological outcome for patients with Q fever vascular infections diagnosed in our center. Between 1986 and February 2015, 100 patients were diagnosed with Q fever vascular infections. The incidence of these infections has significantly increased over the past 5 years, in comparison with the mean annual incidence over the preceding 22 years (8.83 cases per year versus 3.14 cases per year, P   =  0.001). A two-and-a-half-year follow-up was available for 66 patients, of whom 18.2% died. We observed 6.5% of deaths in the group of patients who were operated upon at 2 and a half years, in comparison with 28.6% in the group which were not operated upon ( P   =  0.02). Surgery was the only factor that had a positive impact on survival at 2 and a half years using univariate analysis [hazard ratio: 0.17 [95% CI]: [0.039–0.79]; P  = 0.024]. Surgery was also associated with a good serological outcome (74.1% vs 57.1% of patients, P   =  0.03). In the group of patients with vascular graft infections (n = 47), surgery had a positive impact on serological outcome at 2 and a half years (85.7% vs 42.9%, P  < 0.001) [hazard ratio: 0.40 [95% CI]: [0.17–098]; P  = 0.046] and tended to be associated with lower although not statistically significant mortality (11.1% vs 27.6% of deaths, P   =  0.19). Surgical treatment confers a benefit in terms of survival following C burnetii vascular infections. However, given the high mortality of these infections and their rising incidence, we propose a strategy that consists of screening for vascular graft and aneurysms in the context of primary Q fever, to decide when to start prophylactic treatment, similar to the strategy recommended for the prophylaxis of Q fever endocarditis. Abstract : Supplemental Digital Content is available in the text